2018
DOI: 10.1371/journal.pone.0190155
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent host develops mild intestinal inflammation in acute infection with Toxoplasma gondii

Abstract: Toxoplasma gondii (T. gondii) is the causative agent of toxoplasmosis, common zoonosis among vertebrates and high incidence worldwide. During the infection, the parasite needs to transpose the intestinal barrier to spread throughout the body, which may be a trigger for an inflammatory reaction. This work evaluated the inflammatory alterations of early T. gondii infection in peripheral blood cells, in the mesenteric microcirculation, and small intestinal tissue by measurement of MPO (myeloperoxidase) activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…To our knowledge, only T. gondii has been imaged in the intestines by IVM (Coombes et al, 2013;Watanabe et al, 2018). Altogether, this IVM-based finding is fascinating in that it enabled elucidating a Trojan-horse-like mechanism of pathogen spread which might be highly relevant for other parasites also able to cross tissue barriers.…”
Section: Methods For Ivm-based Visualization Of the Galtmentioning
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, only T. gondii has been imaged in the intestines by IVM (Coombes et al, 2013;Watanabe et al, 2018). Altogether, this IVM-based finding is fascinating in that it enabled elucidating a Trojan-horse-like mechanism of pathogen spread which might be highly relevant for other parasites also able to cross tissue barriers.…”
Section: Methods For Ivm-based Visualization Of the Galtmentioning
confidence: 86%
“…To our knowledge, only T. gondii has been imaged in the intestines by IVM (Coombes et al, ; Watanabe et al, ).…”
Section: Secondary Lymphoid Organs In Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the infection can compromise the intestinal structure and innervation, even in immunocompetent individuals with no classic clinical signs of toxoplasmosis . We observed local inflammation that was possibly induced by the presence of the parasite in the organ, reflected by the presence of tissue cysts and parasitic DNA . The submucosal plexus and EGCs appear to play a primordial role in the response to infection .…”
Section: Introductionmentioning
confidence: 77%
“…[14][15][16][17][18] We observed local inflammation that was possibly induced by the presence of the parasite in the organ, reflected by the presence of tissue cysts and parasitic DNA. [19][20][21] The submucosal plexus and EGCs appear to play a primordial role in the response to infection. 17,22,23 They are able to detect inflammatory stimuli, promote alterations of their phenotype, and modulate the proliferation of other cell types.…”
Section: Introductionmentioning
confidence: 99%